The effects of molecular weight of a new hole transporting polymer on the organic solar cells performance - Li, Xianqiang (2018)
In this research, OSCs based on a new hole transporting polymer were fabricated. The highest power conversion efficiency of the device was received of 6.7% with the optimized molecular weight of the polymer. The charge carrier mobility in the OSCs was measured by using photoinduced charge extraction by linearly increasing voltage (PhotoCELIV) and time-of-flight (TOF) techniques. It is found that the charge carrier mobility is similar in the devices with both high and low molecular weight polymers. Light intensity dependence of the current-voltage characteristics was measured, which indicates strong bimolecular recombination in the low molecular weight polymer devices. Furthermore, the series and bulk resistances of the OSCs were obtained from the impedance measurement of the device. The high molecular device has a lower bulk resistance which corresponds to the weak bimolecular recombination of the device.